An efficient molybdenum disulfide/cobalt diselenide hybrid catalyst for electrochemical hydrogen generation - Gao, Min-Rui; Liang, Jin-Xia; Zheng, Ya-Rong; Xu, Yun-Fei; Jiang, Jun; Gao, Qiang; Li, Jun; Yu, Shu-Hong (Nature communications, 2015)
The electroreduction of water for sustainable hydrogen production is a critical component of several developing clean-energy technologies, such as water splitting and fuel cells. However, finding a cheap and efficient alternative catalyst to replace currently used platinum-based catalysts is still a prerequisite for the commercialization of these technologies. Here we report a robust and highly active catalyst for hydrogen evolution reaction that is constructed by in situ growth of molybdenum disulfide on the surface of cobalt diselenide. In acidic media, the molybdenum disulfide/cobalt diselenide catalyst exhibits fast hydrogen evolution kinetics with onset potential of −11 mV and Tafel slope of 36 mV per decade, which is the best among the non-noble metal hydrogen evolution catalysts and even approaches to the commercial platinum/carbon catalyst. The high hydrogen evolution activity of molybdenum disulfide/cobalt diselenide hybrid is likely due to the electrocatalytic synergistic effects between hydrogen evolution-active molybdenum disulfide and cobalt diselenide materials and the much increased catalytic sites. There is substantial research into new catalysts for electroreduction of water. Here, the authors report a robust and active molybdenum disulfide/cobalt diselenide hydrogen evolution catalyst with onset potential of 11 mV and Tafel slope of 36 mV per decade, approaching the activity of platinum.